2013
DOI: 10.1155/2013/160374
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Military Members: Emerging Issues and Nonpharmacological Intervention

Abstract: Background. Many individuals who work in the military experience sleep deficiency which presents a significant problem given the nature of their work. The cause of their sleep problems is likely multifactorial, stemming from the interplay between their personal health, habits and lifestyle juxtaposed with the stress of their military work such as emotional and physical trauma experienced in service. Objective. To present an overview of sleep deficiency in military members (MMs) and review of nonpharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 52 publications
0
18
0
1
Order By: Relevance
“…individuals, members of the armed forces, and institutional populations may have impacted the prevalence rate of troubled sleep reported in this paper as some studies have found prevalence rates of troubled sleep among these individuals to be high [45,46]. However, given that this population constituted <3% of the sample, their impact, if any, would be minimal on the prevalence rate of troubled sleep reported in this study.…”
Section: Tablementioning
confidence: 81%
“…individuals, members of the armed forces, and institutional populations may have impacted the prevalence rate of troubled sleep reported in this paper as some studies have found prevalence rates of troubled sleep among these individuals to be high [45,46]. However, given that this population constituted <3% of the sample, their impact, if any, would be minimal on the prevalence rate of troubled sleep reported in this study.…”
Section: Tablementioning
confidence: 81%
“…Clarifying the relationship between insomnia and mental disorders is relevant to the health and well-being of military personnel, particularly in the context of deployment, which may affect both mental health and sleep patterns [9][10][11]. Disruptions to the latter can affect mental and physical stamina, cognitive functioning, and operational readiness of troops [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previously deployed soldiers with past-year sleep, depression or alcohol diagnoses were at higher risk for accident death. These conditions are associated with deployment stress exposure and post-deployment adjustment difficulties (Schumm and Chard, 2012; Brown et al, 2013). Consequently, indicators of combat exposure effects, such as health-risk perceptions (Killgore et al, 2008) or post-deployment persistence of combat tactics (e.g., aggressive driving to avoid threat of attacks) (Possis et al, 2014), could further diffierentiate groups at high risk.…”
Section: Resultsmentioning
confidence: 99%